Tank-based scale-up production of the edible seaweed Ulva ohnoi using Ascophyllum extract as a bio-stimulant for functional food - S. Dinesh Kumar; A. Sineka; Abantika Majumder; M. Hariprakash; Komal R. Chilveri; Bhavik Kantilal Bhagiya; R. Suhail Haq; K. Logesh; S. Rithika; S. Nithisha; Khanjan Trivedi; Vaibhav A. Mantri (Bioresource Technology Reports, 2026)

Synergistic effect of germanium dioxide on the edible green seaweed Ulva ohnoi to improve elite biomass production in tank-based cultivation systems - S. Dinesh Kumar; S. Nithisha; Abantika Majumder; R. Suhail Haq; M. Hariprakash; K. Logesh; S. Rithika; A. Sineka (Journal of Applied Phycology, 2025)

High Resolution Sentinel-2 and Sentinel-3 Satellite Imagery in Monitoring Green Noctiluca scintillans Blooms in Complex Coastal Waters: A Case Study in Gulf of Mannar - Logesh Natarajan; Muthukumar Chandrasekaran; Manigandan Vajravelu; Chinmay Shah; Sanitha K. Sivadas; Karri Ramu; M. V. Ramana Murthy (Journal of the Indian Society of Remote Sensing, 2025)

Recurrent Swarms of Planktonic Shrimp Luciferidae De Haan, 1849 (Order: Decapoda) in the Neritic Waters of Tamil Nadu, Southeast Coast of India - R. S. Sathishkumar; B. Charan Kumar; C. Muthukumar; N. Logesh; Sanitha K. Sivadas; K. Ramu; M. V. Ramana Murthy (Marine Ecology, 2024)
Luciferidae (Decapoda) are an important component of mesozooplankton in pelagic food webs. This study investigated the spatiotemporal distribution and frequency of Luciferidae swarms along the Tamil Nadu coast, as observed during coastal monitoring cruises conducted between 2019 and 2022. Data were collected on various hydrobiological factors, including surface water temperature, salinity, chlorophyll a , zooplankton biomass, and the abundance of other mesozooplankton (such as copepods, cladocerans, and others) across eight locations in the coastal waters of Tamil Nadu, India. Salinity values were generally low ( Belzebub hanseni Nobili, 1905, as the only organism responsible for swarm formation, with its occurrence peaking in January 2022. During this period, B. hanseni reached a maximum abundance of 3294 ind. m −3 for adults and 4056 ind. m −3 for larvae, together contributing approximately 27% of the total zooplankton abundance. Swarms of B. hanseni were observed a total of seven times over the course of the study, correlating with periods of low sea surface temperature and high food availability. Pearson's correlation analysis revealed a significant relationship between the abundance of copepods and B. hanseni ( r = 0.84; p B. hanseni in the nearshore waters of the Tamil Nadu coast is largely driven by food availability and optimal environmental conditions, including water temperature and monsoonal influences. The findings also suggest that geographical features, such as mangrove habitats, may contribute to the occurrence of B. hanseni swarms in this region.

Fluorescence enhancing and quenching signal based on new approach for selective detection of multiple organochlorine pesticides using blue emissive-carbon dot - P. Nethaji; P. Revathi; P. Senthil Kumar; M. Logesh; Jothi Ramalingam Rajabathar; H.A. Al-Lohedan; S. Arokiyaraj; Gayathri Rangasamy (Environmental Pollution, 2024)

Implications of equivalent black carbon heterogeneity in south Indian high-altitude eco-sensitive region - B. Logesh; V. Karthik; B. Vijay Bhaskar; E. Ebenezer; M. Arun Kumar (Environmental Monitoring and Assessment, 2023)

Studies on Lichens of Mizoram, Northeast India - A. R. Logesh; M. Chinlampianga; A. C. Shukla; D. K. Upreti (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)